From Disabling Community to Embracing Gospel: - Duma Indah Sinaga (JURNAL LUXNOS, 2023)
Abstract: Biblical text relating to disability usually approached with either a metaphorical or literary interpretation. Both of these approaches themselves provide a negative view of people with disabilities. Both of these approaches show that disability is a condition to be eliminated. This tendency itself arises because of the lack of attention to the context of the Bible itself and the limited approach to understanding disability only in the medical approach. This article comes with an awareness of the gap between the world of the Bible and the modern world. Therefore, using qualitativve methods through literature study, this article aims to explore the message of Luke 14:12-14 with a focus on the social-religious context of the Gospel of Luke, particularly the banquet, the understanding of the body in the Jewish context, and the meaning of sickness and healt, which are examined through the perspective of disability studies. The result is that the text finds alignments with people with disabilities in three form, namely the collapse of normalism, embracing “damaged” bodies, and eating together as an act of solidarity. This article will show that in the text of Luke 14:12-14, physical disability is not something that should be eliminated, but celebrated in communal meal. Abstrak: Teks-teks Alkitab yang berkaitan dengan disabilitas biasanya didekati dengan tafsir metaforis maupun literer. Kedua pendekatan ini memberikan pandangan yang negatif terhadap orang dengan disabilitas. Kedua pendekatan ini menunjukkan bahwa disabilitas adalah keadaan ingin dieliminasi. Kecenderungan ini muncul karena kurangnya perhatian pada konteks Alkitab itu sendiri dan terbatasnya pemahaman tentang disabilitas hanya pada pendekatan model medis. Artikel ini hadir dengan kesadaran bahwa terdapat kesenjangan antara dunia Alkitab dan dunia modern. Oleh sebab itu, dengan menggunakan metode kualitatif melalui studi literatur, artikel ini bertujuan mengupas pesan teks Lukas 14:12-14 dengan perhatian pada konteks sosial religious Injil Lukas khususnya perjamuan makan, pemahaman tentang tubuh dalam konteks Yahudi, serta makna sakit dan sehat yang didialogkan dengan perspektif studi disabilitas. Hasilnya adalah ditemukan keberpihakan teks Lukas 14:12-14 terhadap orang dengan disabilitas dalam tiga rupa, yaitu runtuhnya normalisme, tubuh-tubuh yang rusak direngkuh, dan makan bersama sebagai sebuah aksi solidaritas. Artikel ini akan menunjukkan bahwa dalam teks Lukas 14:12-14, disabilitas fisik bukanlah sesuatu yang harus dieliminasi, namun dirayakan dalam persekutuan makan bersama.